A High-Density Genetic Map of an Allohexaploid Brassica Doubled Haploid Population Reveals Quantitative Trait Loci for Pollen Viability and Fertility - Yang, Su; Chen, Sheng; Zhang, Kangni; Li, Lan; Yin, Yuling; Gill, Rafaqat A.; Yan, Guijun; Meng, Jinling; Cowling, Wallace A.; Zhou, Weijun (Frontiers in Plant Science, 2018)
A doubled haploid (DH) mapping population was obtained from microspore culture of an allohexaploid F1 from the cross between two recently-synthesized allohexaploid Brassica lines. We used single nucleotide polymorphism (SNP) genetic variation based on restriction-site associated DNA (RAD) sequencing to construct a high density genetic linkage map of the population. RAD libraries were constructed from the genomic DNA of both parents and 146 DH progenies. A total of 2.87 G reads with an average sequencing depth of 2.59 × were obtained in the parents and of 1.41 × in the progeny. A total of 290,422 SNPs were identified from clustering of RAD reads, from which we developed 7,950 high quality SNP markers that segregated normally (1:1) in the population. The linkage map contained all 27 chromosomes from the parental A, B and C genomes with a total genetic distance of 5725.19 cM and an average of 0.75 cM between adjacent markers. Genetic distance on non-integrated linkage groups was 1534.23 cM, or 21% of total genetic distance. Out of 146 DH progenies, 91 had a complete set of 27 chromosomes as expected of a hexaploid species, and 21 out of 27 chromosomes showed high collinearity between the physical and linkage maps. The loss of chromosome(s) or chromosome segment(s) in the DH population was associated with a reduction in pollen viability. Twenty-five additive QTL were associated with pollen viability and fertility-related traits (seed number, seed yield, pod length, plant height, 1000-seed weight). In addition, 44 intra-genomic and 18 inter-genomic epistatic QTL pairs were detected for 4 phenotypic traits. This provides confidence that the DH population may be selected for improved pollen viability and fertility in a future allohexaploid Brassica species.